2023
DOI: 10.1097/mco.0000000000000929
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Lipids to support physiology and function: both quantity and quality are important

Abstract: Complex lipids and their fatty acid constituents are found in every cell of the body and in many body fluids and secretions. They play structural, functional and metabolic roles that contribute to physiological homeostasis and to resilience in response to challenges, impacting cell, tissue and whole-body function and fitness, health and wellbeing, and ultimately disease risk. The number of possible lipid structures in any compartment or pool within the body is immense. For example, Quehenberger and Dennis [1] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have shown S. epidermidis skewed T cell response toward a balance that allowed a stalemate between the host and the pathogen, in which the infection can become chronic (73)(74)(75). Oxylipins, such as prostaglandins and leukotrienes, had been extensively studied for their immunomodulatory effects (76). Prostaglandin E2 (PGE2) had been shown to promote the differentiation of naive CD4 T cells into Tregs and skew the immune response toward immunosuppression (77).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…Previous studies have shown S. epidermidis skewed T cell response toward a balance that allowed a stalemate between the host and the pathogen, in which the infection can become chronic (73)(74)(75). Oxylipins, such as prostaglandins and leukotrienes, had been extensively studied for their immunomodulatory effects (76). Prostaglandin E2 (PGE2) had been shown to promote the differentiation of naive CD4 T cells into Tregs and skew the immune response toward immunosuppression (77).…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%